2019
DOI: 10.1186/s12885-019-5587-3
|View full text |Cite
|
Sign up to set email alerts
|

Advanced assessment of migration and invasion of cancer cells in response to mifepristone therapy using double fluorescence cytochemical labeling

Abstract: Background Previous work in our laboratory demonstrated that antiprogestin mifepristone impairs the growth and adhesion of highly metastatic cancer cells, and causes changes in their cellular morphology. In this study, we further assess the anti-metastatic properties of mifepristone, by studying whether cytostatic doses of the drug can inhibit the migration and invasion of various cancer cell lines using a double fluorescence cytochemical labeling approach. Methods Cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 44 publications
0
32
0
Order By: Relevance
“…One attractive candidate for repositioning is mifepristone, a synthetic steroid that serves as an abortifacient drug based on anti-progestational and anti-glucocorticoid action. Mifepristone reportedly has antiproliferative effects in breast ( 15 , 16 ), cervix ( 17 ), endometrium ( 18 ), ovary ( 19 ), and prostate cancer ( 20 ), can cross the BBB, and provides palliative effects on brain tumors such as meningiomas ( 21 ) and glioblastoma ( 22 ). Additionally, it is considered safe (with few adverse effects) and has a low cost.…”
Section: Introductionmentioning
confidence: 99%
“…One attractive candidate for repositioning is mifepristone, a synthetic steroid that serves as an abortifacient drug based on anti-progestational and anti-glucocorticoid action. Mifepristone reportedly has antiproliferative effects in breast ( 15 , 16 ), cervix ( 17 ), endometrium ( 18 ), ovary ( 19 ), and prostate cancer ( 20 ), can cross the BBB, and provides palliative effects on brain tumors such as meningiomas ( 21 ) and glioblastoma ( 22 ). Additionally, it is considered safe (with few adverse effects) and has a low cost.…”
Section: Introductionmentioning
confidence: 99%
“…RU486 was found to decrease migration and invasion of glia (U87MG), ovary (SKOV-3), breast (MDA-MB231), and prostate (LNCaP) cancer cells (26). Moreover, it was also demonstrated that treatment with RU486 induces a distinct pattern of migration in these different cell lines, as well as for nuclear location during migration and the apparent redistribution of F-actin to the nucleus (26).…”
Section: Discussionmentioning
confidence: 98%
“…With regard to the effect on tumor growth, while the steroid antagonist treatment caused a significant retardation of tumor progression, a complete inhibition or prevention of tumor growth did not occur. However, RU486 could possibly act as regulator of tumor metastatic diffusion, since an inhibitory effect of the RU486 in vivo on cancer metastasis has been described (26). Moreover, RU486 may be used as an adjuvant or a chemo-sensitizing agent in association with more conventional anticancer drugs, as suggested by a number of reports.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the clinic, steroidal PR agonists have been used in oral contraception and postmenopasusal hormone therapy (Fensome et al, 2005;Afhüppe et al, 2009;Lee et al, 2020). In addition, PR antagonists are gaining attention as a potential anti-cancer treatment due to their inhibitory effects on cell growth in vitro, affecting ovarian, breast, prostate, and bone cancer cells (Tieszen et al, 2011;Zheng et al, 2017;Ponikwicka-Tyszko et al, 2019;Ritch et al, 2019;Trabert et al, 2019). However, recent clinical trials on ovarian cancer with a selective progesterone receptor modulator, such as mifepristone, have largely been unsuccessful, despite high in vitro antagonist activity in nuclear PR (Rocereto et al, 2010;Ponikwicka-Tyszko et al, 2019).…”
Section: Introductionmentioning
confidence: 99%